Synthesis and characterization of lithium - substituted of magnesium oxide / Siti Nur Hazlinda Hasbu - Hasbu, Siti Nur Hazlinda (Faculty of Applied Sciences, 2010)
Lithium substituted of magnesium oxide compounds were prepared via sol-gel method using magnesium acetate tetrahydrate and lithium acetate dehydrate as starting materials and oxalic acid as gelating agent. Five different composition of lithium substituted magnesium oxide; Li₀.₂ Mg₀.₉O, Li₀.₄Mg₀.₈O, Li₀.₆Mg₀.₇O, Li₀.₈Mg₀.₆O and Li₁.₀Mg₀.₅O were prepared. The powder obtained was annealed at 950°C for 24 and 36 hours. The characterizations of these compounds were analyzed by using Thermal Gravimetric Analyzer, X-Ray Diffractometer and Scanning Electron Microscopy. The thermal study of magnesium oxide showed the temperature for stable formation of MgO was 500 °C and above. The results showed that, at 950 °C for 24 hours, only three different compositions of substituted compounds were accomplished, which were Li₀.₂Mg₀.₉O, Li₀.₄Mg₀.₈O and Li₀.₆Mg₀.₇O. By increasing the annealing time into 36 hours for the same annealing temperature, pure products of Li₀.₈Mg₀.₆O and Li₁.₀Mg₀.₅O were obtained with other compositions except for Li₀.₄Mg₀.₈O. The morphology of MgO and their substituted MgO were changed from flower-like into rock-like by increasing the amount of lithium ion in the metal oxide matrix.